Bismarck versus Beveridge: Flat- and earnings-related unemployment insurance in an efficiency wage framework - Laszlo Goerke (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1998)
A higher unemployment compensation increases the incentive to shirk in efficiency wage models. If there is a stronger dependence of unemployment benefits on current earnings, these incentives will be reduced. An unemployment insurance with earnings-related benefits is thus characterised by higher employment than one with flat-rate benefits. It is investigated under which conditions this advantage persists in the longer term when financial constraints such as an ex-post constant level of benefits, a cash hmit or a balanced budget rule apply, or when firms are constrained to zero profits.
Keywords: H24; H25; J32; J41; J65; 330; balanced budget; cash limit; earnings-related benefits; efficiency wages; flat-rate benefits; long-run; unemployment insurance